THE INFLUENCE OF WORK ENVIRONMENT AND COMPENSATION ON JOB SATISFACTION OF GEN Z EMPLOYEES IN MSMEs IN PALEMBANG - Saputra, Dhaniel Whizztyo (Dynamic Management Journal, 2024)
In the face of contemporary digitalization, businesses must be well-prepared to navigate competitive landscapes. Despite this, many businesses, especially MSMEs, grapple with addressing employee dissatisfaction. This research aimed to assess the influence of workplace environment (X1) and compensation (X2) on job satisfaction among Generation Z employees in Micro, Small, and Medium Enterprises (MSMEs) in Palembang. Focusing on Generation Z employees within the MSMEs of Palembang, the research utilized purposive sampling, accumulating a total of 90 samples. Employing multiple linear regression analysis through SPSS version 26, the study's outcomes reveal that: (1) the work environment variable (X1) significantly and positively impacts job satisfaction among Generation Z employees in MSMEs in Palembang; and (2) Compensation (X2) also plays a positive and significant role in enhancing the job satisfaction of Generation Z employees. These findings provide valuable insights for businesses grappling with challenges in the digital era, emphasizing the importance of fostering a conducive work environment and competitive compensation to ensure employee satisfaction.